Pembangunan Jalan Bebas Hambatan Ibu Kota Negara Segmen Jembatan Pulau Balang – SP. Riko - Salman; Marnida; Toto (PT. Hasba Edukasi Mandiri, 2025)
The construction of the Nusantara Capital City (IKN) Expressway, Segment Pulau Balang Bridge – Sp. Riko, is part of the toll road network supporting accessibility in East Kalimantan Province. In this project, a geotechnical analysis was conducted on the embankment at STA 1+325 to STA 1+475 to ensure the stability and bearing capacity of the subsoil. The investigation results indicate that the surface soil conditions in the area exhibit low stability characteristics, with an average cone resistance (qc) value ranging from 4 to 8 kg/cm² at a depth of 2 meters, indicating very soft to soft soil consistency. To address the soil bearing capacity issue, various improvement methods were applied, including subsoil replacement with granular material up to 2 meters thick and stability analysis using PLAXIS 2D software. The modeling results show that the safety factor without treatment was 1.350 under service conditions and 1.116 under seismic conditions, which did not meet design criteria. After implementing the 2-meter replacement method, the safety factor increased to 1.715 under service conditions and 1.258 under seismic conditions, thus meeting stability standards. Therefore, the 2.0-meter replacement method is recommended as an effective solution to enhance the bearing capacity and embankment stability in the study area.